Understanding green technology from Malaysian online news - Haroon, Harshita Aini; Nordin, Norshahrizan; Abdullah, Mohd Mustafa Al Bakri; Marniati, Marniati (AIP conference proceedings, 2020)
Malaysia's commitment to a green Malaysia is unquestionable, particularly with the inception of the National Green Technology Policy a decade ago. One of the key objectives of the policy is raising the awareness of, and educating the general public on green technology since their understanding of it will influence how they receive relevant initiatives. This study, therefore, explores how green technology is portrayed in online news as it is a source of information on the subject. We asked what messages are projected, and particularly if the idea of collaborative efforts required for the success of green technology initiatives is reflected in the news. A scrutiny of 35 news pieces yielded from an internet search suggests that there is low public interest on green technology. The message conveyed to the public is that green technology is commonly the “job” of the government, with very little relevance to the individual. While notions of collaboration between key players are relayed through the news, the scarcity of reporting on the role of academia is of concern.